Protein kinase D selectively targets cardiac troponin I and regulates myofilament Ca2+ sensitivity in ventricular myocytes - Cuello, Friederike; Bardswell, Sonya C.; Haworth, Robert S.; Yin, Xiaoke; Lutz, Susanne; Wieland, Thomas; Mayr, Manuel; Kentish, Jonathan C.; Avkiran, Metin (Circulation research, 2007)
Protein kinase D ( PKD) is a serine/threonine kinase with emerging myocardial functions; in skinned adult rat ventricular myocytes ( ARVMs), recombinant PKD catalytic domain phosphorylates cardiac troponin I at Ser22/Ser23 and reduces myofilament Ca2+ sensitivity. We used adenoviral gene transfer to determine the effects of full-length PKD on protein phosphorylation, sarcomere shortening and [ Ca2+](i) transients in intact ARVMs. In myocytes transduced to express wild-type PKD, the heterologously expressed enzyme was activated by endothelin 1 ( ET1) ( 5 nmol/L), as reflected by PKD phosphorylation at Ser744/Ser748 ( PKC phosphorylation sites) and Ser916 ( autophosphorylation site). The ET1-induced increase in cellular PKD activity was accompanied by increased cardiac troponin I phosphorylation at Ser22/Ser23; this measured approximately 60% of that induced by isoproterenol ( 10 nmol/L), which activates cAMP-dependent protein kinase ( PKA) but not PKD. Phosphorylation of other PKA targets, such as phospholamban at Ser16, phospholemman at Ser68 and cardiac myosin-binding protein C at Ser282, was unaltered. Furthermore, heterologous PKD expression had no effect on isoproterenol-induced phosphorylation of these proteins, or on isoproterenol-induced increases in sarcomere shortening and relaxation rate and [ Ca2+](i) transient amplitude. In contrast, heterologous PKD expression suppressed the positive inotropic effect of ET1 seen in control cells, without altering ET1-induced increases in relaxation rate and [ Ca2+](i) transient amplitude. Complementary experiments in "skinned" myocytes confirmed reduced myofilament Ca2+ sensitivity by ET1-induced activation of heterologously expressed PKD. We conclude that increased myocardial PKD activity induces cardiac troponin I phosphorylation at Ser22/Ser23 and reduces myofilament Ca2+ sensitivity, suggesting that altered PKD activity in disease may impact on contractile function.
Gesehen am 24.03.2022
Im Text ist "2+" hochgestellt